Preparation, characterization, in vitro drug release, and cellular interactions of tailored paclitaxel releasing polyethylene oxide films for drug-coated balloons. (1st January 2016) - Anderson, Jordan A.; Lamichhane, Sujan; Remund, Tyler; Kelly, Patrick; Mani, Gopinath
Graphical abstract: Abstract: Drug-coated balloons (DCBs) are used to treat various cardiovascular diseases. Currently available DCBs carry drug on the balloon surface either solely or using different carriers. Several studies have shown that a significant amount of drug is lost in the blood stream during balloon tracking to deliver only a sub-therapeutic level of drug at the treatment site. This research is focused on developing paclitaxel (PAT) loaded polyethylene oxide (PEO) films (PAT–PEO) as a controlled drug delivery carrier for DCBs. An array of PAT–PEO films were developed in this study to provide tailored release of >90% of drug only at specific time intervals, which is the time frame required for carrying out balloon-based therapy. The characterizations of PAT–PEO films using SEM, FTIR, and DSC showed that the films developed were homogenous and the PAT was molecularly dispersed in the PEO matrix. Mechanical tests showed that most PAT–PEO films developed were flexible and ductile, with yield and tensile strengths not affected after PAT incorporation. The viability, proliferation, morphology, and phenotype of smooth muscle cells (SMCs) interacted with control-PEO and PAT–PEO films were investigated. All control-PEO and PAT–PEO films showed a significant inhibitory effect on the growth of SMCs, with the degree of inhibition strongly dependent on the w/v% of the polymer used. The PAT–PEO coating was produced on the balloons. The integrity of PAT–PEO coating was well maintained without any mechanical defects occurring during balloon inflation or deflation. The drug release studies showed that only 15% of the total PAT loaded was released from the balloons within the initial 1 min (typical balloon tracking time), whereas 80% of the PAT was released between 1 min and 4 min (typical balloon treatment time). Thus, this study demonstrated the use of PEO as an alternate drug delivery system for the balloons. Statement of Significance: Atherosclerosis is primarily responsible for cardiovascular diseases (CVDs) in millions of patients every year. Drug-coated balloons (DCBs) are commonly used to treat various CVDs. However, in several currently used DCBs, a significant amount of drug is lost in the blood stream during balloon tracking to deliver only a sub-therapeutic level of drug at the treatment site. In this study, paclitaxel containing polyethylene oxide (PEO) films were developed to provide unique advantages including drug release profiles specifically tailored for balloon-based therapy, homogeneous films with molecularly dispersed drug, flexible and ductile films, and exhibits significant inhibitory effect on smooth muscle cell growth. Thus, this study demonstrated the use of PEO as an alternate drug delivery platform for DCBs to improve its efficacy.